HUBUNGAN POLA ASUH, PENGETAHUAN GIZI, DAN STATUS PEKERJAAN IBU DENGAN PRAKTIK PEMBERIAN MP-ASI PADA BAYI 6-24 BULAN - Gustina Delkis Sitompul; Siti Arofah Siregar; Noer Halimah Harahap; Asmanita Asmanita; Berdina Fifi Yanti Sinaga; Ida Novia Harahap (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2026)
Early introduction of complementary foods (early CF) before four months of age increases the risk of malnutrition fivefold compared to timely introduction at six months. This study aims to analyze the relationship between parenting styles, nutritional literacy, and maternal occupational status regarding complementary feeding (CF) practices among children aged 6 to 24 months at the Sipiongot Community Health Center, North Padang Lawas Regency. This analytic study employed a cross-sectional approach involving 58 respondents. This design was selected to observe the inter-variable relationships simultaneously. Data revealed that the majority of respondents exhibited poor parenting categories (62.1%), moderate nutritional knowledge (50.0%), unemployment status (63.8%), and inadequate CF practices (55.2%). Bivariate analysis demonstrated significant correlations between CF practices and parenting style (p=0.045), nutritional knowledge (p=0.029), and occupational status (p=0.014). Maternal internal factors and employment status play a pivotal role in infant nutritional success. Massive nutritional education and targeted support for stay-at-home mothers are required to improve CF practices in this region.